A low dielectric loss insulation cable based on crosslinked polyethylene

CN122941077APending Publication Date: 2026-10-20GUANGZHOU PANYU CABLE WORKS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611357777.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]目前,交联聚乙烯绝缘材料通常通过加入抗氧剂、无机填料、电稳定剂或有机硅助剂等方式,改善其耐热老化性能和电性能,而无机填料如氮化硼等具有较好的绝缘性和导热性,能够在一定程度上改善绝缘层的散热和电稳定性,但是,氮化硼表面化学活性较低,与聚乙烯基体之间相容性和界面结合力不足,直接加入时容易出现团聚、界面空隙和局部极化区域,反而可能导致介质损耗升高,并且普通抗氧剂多以小分子形式分散在体系中,长期热老化过程中容易迁移、析出或消耗,抗老化作用难以持续稳定;

Benefits of technology

[0024]1、本发明是通过在低密度聚乙烯、线性低密度聚乙烯体系中同时引入活化改性抗老粒子和二苯甲酮改性聚硅氧烷,并通过过氧化物热交联使其稳定结合于聚乙烯交联网络中,使得功能组分能够在绝缘层中较均匀地分散并被网络结构固定,减少填料团聚、界面空隙、小分子迁移和局部介电损耗区域,从而使电缆芯绝缘层同时具有较高的体积电阻率、较低的介质损耗角正切值以及较好的老化后性能保持能力,其与填充层、包带层、铠装层和外护套层相互配合,获得低介质损耗绝缘电缆。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a low dielectric loss insulated cable based on cross-linked polyethylene, belonging to the field of insulated cable technology. It primarily addresses the technical problem that the insulation performance, dielectric loss, and heat aging resistance of cable core materials need further improvement. Specifically, it includes several cable cores, a filler layer, a wrapping layer, and an outer sheath. The cable core comprises a conductor and a cross-linked polyethylene insulation layer covering the conductor. This invention significantly improves the insulation performance and heat aging resistance of the cable core material while reducing the dielectric loss tangent through a compounding of activated modified anti-aging particles, benzophenone-modified polysiloxane, low-density polyethylene, linear low-density polyethylene, and a peroxide cross-linking agent. This combination, along with the filler layer, wrapping layer, armor layer, and outer sheath, results in a low dielectric loss insulated cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulated cable technology, and more specifically to a low dielectric loss insulated cable based on cross-linked polyethylene. Background Technology

[0002] Cross-linked polyethylene (XLPE) insulated cables have been widely used in power transmission, industrial power distribution, and building power supply due to their good electrical insulation, heat resistance, and processing performance. As a key insulation structure in the cable core, the XLPE insulation layer directly affects the safety and stability of the cable during long-term operation due to its volume resistivity, dielectric loss tangent, and mechanical property retention rate after thermal aging.

[0003] Currently, cross-linked polyethylene insulation materials are typically improved in terms of heat aging resistance and electrical properties by adding antioxidants, inorganic fillers, electrical stabilizers, or organosilicon additives. Inorganic fillers such as boron nitride have good insulation and thermal conductivity, which can improve the heat dissipation and electrical stability of the insulation layer to a certain extent. However, boron nitride has low surface chemical activity and insufficient compatibility and interfacial bonding with the polyethylene matrix. When added directly, it is easy to cause agglomeration, interfacial voids, and local polarization regions, which may lead to increased dielectric loss. In addition, most common antioxidants are dispersed in the system in the form of small molecules, which are prone to migration, precipitation, or consumption during long-term thermal aging, making it difficult to maintain a stable anti-aging effect.

[0004] While some electrical stabilizers or organosilicon modifiers can reduce dielectric loss, if their compatibility with the polyethylene matrix is ​​insufficient, they can easily form phase separation regions, affecting the electrical properties and mechanical continuity of the insulation layer. In addition, during long-term operation and hot air aging, the filler interface, additive dispersion area and polyethylene matrix are prone to loosening of the bond, microcrack propagation and local dielectric inhomogeneity, which ultimately manifest as a decrease in volume resistivity, an increase in dielectric loss tangent, and a decrease in the retention rate of tensile strength and elongation at break.

[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a low dielectric loss insulated cable based on cross-linked polyethylene to address the aforementioned technical deficiencies.

[0007] The objective of this invention can be achieved through the following technical solution: a low dielectric loss insulated cable based on cross-linked polyethylene, comprising a plurality of cable cores, a filler layer, a wrapping layer and an outer sheath layer, wherein the cable cores comprise a conductor and a cross-linked polyethylene insulation layer covering the conductor.

[0008] The cross-linked polyethylene insulation layer comprises the following components by weight: 80-85 parts of low-density polyethylene, 15-18 parts of linear low-density polyethylene, 6-8 parts of activated modified anti-aging particles, 11-16 parts of benzophenone-modified polysiloxane, 0.8-1.6 parts of initiator, and 2-3 parts of additives.

[0009] Furthermore, the initiator is di-tert-butylperoxyisopropylbenzene.

[0010] Furthermore, the additives are composed of stearate, ethylene bis-stearamide, phthalate, antioxidant 1010, and antioxidant 168 in a weight ratio of 5:3:4:2:1.

[0011] Furthermore, the preparation method of activated modified anti-aging particles is as follows: under the protection of an inert gas atmosphere, dopamine modified particles and anhydrous toluene are mixed and stirred, the reaction system is cooled to 0-5℃, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 4-chloropentenol and triethylamine are added to the reaction system, the mixture is kept warm and stirred for 90-120 min, the reaction system is heated to 60-70℃, the reaction is kept warm for 6-8 h, and then post-processed to obtain activated modified anti-aging particles.

[0012] Furthermore, the ratio of the dopamine-modified particles, anhydrous toluene, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 4-chloropentenol, and triethylamine is 10g:500mL:1.0-1.2g:0.5-0.7g:1-1.6g. The post-treatment includes: after the reaction is complete, the reaction system is cooled to room temperature, filtered, the filter cake is washed three times with purified water and then dried, the filter cake is transferred to a drying oven at 65-75℃ and dried to constant weight to obtain activated modified anti-aging particles.

[0013] Furthermore, the preparation method of dopamine-modified particles is as follows: magnesium-aluminum composite boron nitride and Tris buffer are mixed and ultrasonically dispersed for 30-50 min. Dopamine hydrochloride is added to the reaction system, and the mixture is stirred at room temperature for 6-8 h. After post-treatment, dopamine-modified particles are obtained.

[0014] Furthermore, the ratio of the magnesium-aluminum composite boron nitride, Tris buffer, and dopamine hydrochloride is 10g:800-1000mL:2-3g, the concentration of the Tris buffer is 0.01mol / L, and the pH is 8.5. The post-treatment includes: after the reaction is complete, filtration is performed, the filter cake is washed with purified water until neutral, and then dried. The filter cake is transferred to a drying oven at a temperature of 65-75℃ and dried to constant weight to obtain dopamine-modified particles.

[0015] Furthermore, the preparation method of magnesium-aluminum composite boron nitride is as follows: magnesium chloride, aluminum chloride and deionized water are mixed and stirred until the system is dissolved. Boron nitride is added to the reaction system and ultrasonically dispersed for 30-50 min. At room temperature, sodium hydroxide solution is added dropwise to the reaction system to adjust the pH of the system to 9-10. The reaction system is heated to 70-80℃ and allowed to stand for aging for 6-8 h. After post-treatment, magnesium-aluminum composite boron nitride is obtained.

[0016] Furthermore, the ratio of magnesium chloride, aluminum chloride, deionized water, and boron nitride is 2-3g:0.8-1.2g:100mL:15g, and the concentration of the sodium hydroxide solution is 0.3-0.5mol / L. The post-treatment includes: after the reaction is complete, the reaction system is cooled to room temperature, filtered, the filter cake is washed with purified water until neutral, the filter cake is transferred to an atmosphere furnace, and the atmosphere furnace is heated to 80-90℃ in an air atmosphere and dried for 3-4 hours. Then the atmosphere furnace is heated to 450-500℃ and calcined for 60-80 minutes, and then cooled naturally to room temperature to obtain magnesium-aluminum composite boron nitride.

[0017] Furthermore, benzophenone-modified polysiloxane is obtained by the following steps:

[0018] A1. Under an inert gas atmosphere, 2-aminobenzophenone and tetrahydrofuran were mixed and stirred to dissolve. The reaction system was heated to 50-60℃, and 3-isocyanate methyl diethoxysilane was added to the reaction system. The reaction was kept at the temperature for 60-80 min. After post-treatment, diethoxysilane-modified benzophenone was obtained.

[0019] A2. Mix and stir octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, dodecylmethyldiethoxysilane, diethoxysilane-modified benzophenone, and sulfuric acid. Heat the reaction system to 85-95℃ and keep it at that temperature for 2-3 hours. Add diallyltetramethyldisiloxane to the reaction system and keep it at that temperature for 4-5 hours. After post-treatment, benzophenone-modified polysiloxane is obtained.

[0020] Further, in step A1, the ratio of 2-aminobenzophenone to tetrahydrofuran is 1g:10mL, the molar ratio of 2-aminobenzophenone to 3-isocyanate methyl diethoxysilane is 1:1, and the post-treatment includes: after the reaction is completed, the reaction system is subjected to negative pressure, and low-boiling substances are removed by vacuum evaporation to obtain diethoxysilane-modified benzophenone.

[0021] Further, in step A2, the ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, dodecylmethyldiethoxysilane, diethoxysilane-modified benzophenone, sulfuric acid, and diallyltetramethyldisiloxane is 100g:10-15g:8-12g:17-20g:5-8mL:5-7g, and the mass fraction of sulfuric acid is 75-85%. The post-treatment includes: after the reaction is complete, cooling the reaction system to room temperature, adding 3-5wt% sodium bicarbonate aqueous solution to the reaction system, adjusting the pH of the system to 7-8, allowing it to stand and separate the liquids, washing the oily substance three times with purified water, and then transferring it to a rotary evaporator with a water bath temperature of 85-95℃ to remove low-boiling substances under reduced pressure to obtain benzophenone-modified polysiloxane.

[0022] Furthermore, the cable core is prepared by: melting and mixing low-density polyethylene, linear low-density polyethylene, activated modified anti-aging particles, benzophenone modified polysiloxane, and additives for 10-15 minutes, cooling to room temperature, and pulverizing to obtain a polyethylene premix; mixing the polyethylene premix with an initiator evenly and adding it to a twin-screw extruder, melting and mixing for 40-70 seconds, extruding and coating the conductor, and then performing a thermal crosslinking treatment at 175-200℃ for 6-8 minutes followed by air cooling and curing to form a crosslinked polyethylene insulation layer with a thickness of 3.0±0.1 mm on the outside of the conductor.

[0023] The present invention has the following beneficial effects:

[0024] 1. This invention introduces activated modified anti-aging particles and benzophenone-modified polysiloxane into a low-density polyethylene and linear low-density polyethylene system, and then uses peroxide thermal crosslinking to stably bind them into the polyethylene crosslinking network. This allows the functional components to be more uniformly dispersed in the insulation layer and fixed by the network structure, reducing filler agglomeration, interfacial voids, small molecule migration, and local dielectric loss areas. As a result, the cable core insulation layer has high volume resistivity, low dielectric loss tangent, and good performance retention after aging. It works in conjunction with the filler layer, wrapping layer, armor layer, and outer sheath layer to obtain a low dielectric loss insulated cable.

[0025] 2. This invention also employs magnesium-aluminum composite and dopamine coating to modify the interface of boron nitride, and further grafts hindered phenolic and alkenyl structures to obtain activated modified anti-aging particles. The magnesium-aluminum composite layer can improve the surface activity and interfacial bonding ability of boron nitride, while the dopamine layer plays a role in transition coating and subsequent grafting reactions. The hindered phenolic structure can capture free radicals generated by polyethylene oxidation during thermal aging, while the alkenyl structure can participate in cross-linking or grafting reactions during peroxide cross-linking. This allows the activated modified anti-aging particles to simultaneously undertake the functions of insulation and thermal conductivity, interface bridging, antioxidant protection, and cross-linking fixation, thereby reducing the common interfacial polarization and mechanical weakness problems after the introduction of inorganic fillers, and effectively inhibiting the increase in dielectric loss and the degradation of mechanical properties after hot air aging.

[0026] 3. This invention further incorporates the benzophenone structure into a polysiloxane system via a silanization reaction, yielding a benzophenone-modified polysiloxane containing benzophenone electrically stabilizing groups, flexible siloxane segments, long-chain alkyl compatible segments, and vinyl and allyl unsaturated reactive groups. The benzophenone structure helps improve the stability of the material under an electric field, the siloxane segments improve the system's flexibility, the long-chain alkyl segments enhance its compatibility with the polyethylene matrix, and the unsaturated reactive groups facilitate its fixation in the insulating layer during crosslinking. This makes the benzophenone-modified polysiloxane less prone to migration or local accumulation, thus enabling it to more stably reduce dielectric loss and improve aging resistance. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] In this invention, the boron nitride is commercially available hexagonal boron nitride with a particle size of 50-100 nm and a content of ≥99.9%;

[0029] In this invention, the low-density polyethylene is a commercially available product, the processing grade is injection molding grade, and the brand is Sinopec;

[0030] In this invention, linear low-density polyethylene is a commercially available product, with a processing grade of injection molding, a grade of 1I70A, and a brand of Yanshan Petrochemical.

[0031] Preparation Example 1

[0032] This preparation example provides a method for preparing activated modified anti-aging particles, including the following steps:

[0033] Step 1: Preparation of magnesium-aluminum composite boron nitride

[0034] Weigh out 20g of magnesium chloride, 8g of aluminum chloride, and 1L of deionized water and add them to a reaction flask. Stir until the system is dissolved. Add 150g of boron nitride to the reaction flask and sonicate for 30min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. At room temperature, add 0.3mol / L sodium hydroxide solution dropwise to the reaction flask to adjust the pH of the system to 9. Heat the reaction flask to 70℃ and let it stand for aging for 6h. Cool the reaction flask to room temperature and filter. Wash the filter cake with purified water until neutral. Transfer the filter cake to an atmosphere furnace and heat it to 80℃ in an air atmosphere for 3h. Then heat the atmosphere furnace to 450℃ and calcine for 60min. Let it cool naturally to room temperature to obtain magnesium-aluminum composite boron nitride.

[0035] In the reaction, magnesium chloride and aluminum chloride, after dissolving, respectively provide Mg. 2+ And Al 3+ After adding sodium hydroxide and adjusting the system to alkaline conditions, Mg 2+ Al 3+ Hydrolysis and precipitation occur, forming a magnesium and aluminum hydroxide deposit layer in situ on the surface of boron nitride particles. After aging at elevated temperatures, the deposit layer further grows and stabilizes, allowing it to adhere more uniformly to the surface of boron nitride. Subsequently, after drying in an air atmosphere and calcining, the magnesium and aluminum hydroxide on the surface dehydrates and transforms into a magnesium-aluminum composite oxide layer.

[0036] Step 2: Preparation of dopamine-modified particles

[0037] Weigh out 200g of magnesium-aluminum composite boron nitride and 1.6L of 0.01mol / L Tris buffer solution (pH=8.5) and add them to the reaction flask. Sonicate the mixture for 30min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. Add 40g of dopamine hydrochloride to the reaction flask and stir at room temperature for 6h. Filter the mixture and wash the filter cake with purified water until neutral. Dry the filter cake and transfer it to a drying oven at 65℃. Dry the filter cake to constant weight to obtain dopamine-modified particles.

[0038] In the reaction, dopamine undergoes oxidative self-polymerization in Tris buffer to form a polydopamine coating layer. This polydopamine coating layer structurally acts as an intermediate bridge, connecting magnesium-aluminum composite boron nitride on the inner side and providing hydroxyl and amino groups for further reaction on the outer side. This transforms the inorganic particle surface from an inert surface into an interface layer with organic reactivity, which is beneficial for its dispersion in the polyethylene system and reduces the interfacial polarization problem that easily occurs when inorganic fillers are directly added.

[0039] Step 3: Preparation of activated and modified anti-aging particles

[0040] Weigh 200g of dopamine-modified particles and 10L of anhydrous toluene and add them to an argon-protected reactor. Stir the reactor and cool it to 0℃. Add 20g of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 10g of 4-chloropentenol and 20g of triethylamine to the reactor. Keep the mixture warm and stir for 90min. Heat the reactor to 60℃ and keep it warm for 6h. Cool the reactor to room temperature and filter the mixture. Wash the filter cake three times with purified water and dry it. Transfer the filter cake to a drying oven at 65℃ and dry it to constant weight to obtain activated modified anti-aging particles.

[0041] In the reaction, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and 4-chloropentenol undergo amidation with the amino and hydroxyl groups on the polydopamine layer, grafting the hindered phenolic antioxidant structure and alkenyl groups onto the particle surface. Triethylamine mainly absorbs the hydrogen chloride generated in the reaction and promotes the participation of surface nucleophilic groups in the reaction. This results in particles that are no longer just ordinary fillers, but composite functional particles simultaneously possessing a boron nitride insulating and thermally conductive framework, a magnesium-aluminum activated interface, a dopamine transition layer, a hindered phenolic antioxidant structure, and an alkenyl crosslinking active structure.

[0042] Preparation Example 2

[0043] This preparation example provides a method for preparing activated modified anti-aging particles, including the following steps:

[0044] Step 1: Preparation of magnesium-aluminum composite boron nitride

[0045] Weigh out 25g of magnesium chloride, 10g of aluminum chloride, and 1L of deionized water and add them to a reaction flask. Stir until the system is dissolved. Add 150g of boron nitride to the reaction flask and sonicate for 40min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. At room temperature, add 0.4mol / L sodium hydroxide solution dropwise to the reaction flask to adjust the pH of the system to 9.5. Heat the reaction flask to 75℃ and let it stand for 7h. Cool the reaction flask to room temperature and filter. Wash the filter cake with purified water until neutral. Transfer the filter cake to an atmosphere furnace and heat it to 85℃ in an air atmosphere. Dry it for 3.5h. Then heat the atmosphere furnace to 475℃ and calcine it for 70min. Let it cool naturally to room temperature to obtain magnesium-aluminum composite boron nitride.

[0046] Step 2: Preparation of dopamine-modified particles

[0047] Weigh out 200g of magnesium-aluminum composite boron nitride and 1.8L of 0.01mol / L Tris buffer solution (pH=8.5) and add them to a reaction flask. Sonicate the mixture for 40min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. Add 50g of dopamine hydrochloride to the reaction flask and stir at room temperature for 7h. Filter the mixture and wash the filter cake with purified water until neutral. Dry the filter cake and transfer it to a drying oven at 70℃. Dry the filter cake to constant weight to obtain dopamine-modified particles.

[0048] Step 3: Preparation of activated and modified anti-aging particles

[0049] Weigh 200g of dopamine-modified particles and 10L of anhydrous toluene and add them to an argon-protected reactor. Stir the reactor and cool it to 3°C. Add 22g of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 12g of 4-chloropentenol and 26g of triethylamine to the reactor. Keep the reactor warm and stir for 105min. Heat the reactor to 65°C and keep it warm for 7h. Cool the reactor to room temperature and filter. Wash the filter cake three times with purified water and dry it. Transfer the filter cake to a drying oven at 70°C and dry it to constant weight to obtain activated modified anti-aging particles.

[0050] Preparation Example 3

[0051] This preparation example provides a method for preparing activated modified anti-aging particles, including the following steps:

[0052] Step 1: Preparation of magnesium-aluminum composite boron nitride

[0053] Weigh out 30g of magnesium chloride, 12g of aluminum chloride, and 1L of deionized water and add them to a reaction flask. Stir until the system is dissolved. Add 150g of boron nitride to the reaction flask and sonicate for 50min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. At room temperature, add 0.5mol / L sodium hydroxide solution dropwise to the reaction flask to adjust the pH of the system to 10. Heat the reaction flask to 80℃ and let it stand for aging for 8h. Cool the reaction flask to room temperature and filter. Wash the filter cake with purified water until neutral. Transfer the filter cake to an atmosphere furnace and heat it to 90℃ in an air atmosphere for 4h. Then heat the atmosphere furnace to 500℃ and calcine for 80min. Let it cool naturally to room temperature to obtain magnesium-aluminum composite boron nitride.

[0054] Step 2: Preparation of dopamine-modified particles

[0055] Weigh out 200g of magnesium-aluminum composite boron nitride and 2L of 0.01mol / L Tris buffer solution (pH=8.5) and add them to a reaction flask. Sonicate the mixture for 50min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. Add 60g of dopamine hydrochloride to the reaction flask and stir for 8h at room temperature. Filter the mixture and wash the filter cake with purified water until neutral. Dry the filter cake and transfer it to a drying oven at 75℃. Dry the filter cake to constant weight to obtain dopamine-modified particles.

[0056] Step 3: Preparation of activated and modified anti-aging particles

[0057] Weigh 200g of dopamine-modified particles and 10L of anhydrous toluene and add them to an argon-protected reactor. Stir the reactor and cool it to 5°C. Add 24g of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 14g of 4-chloropentenol and 32g of triethylamine to the reactor. Keep the reactor warm and stir for 120min. Heat the reactor to 70°C and keep it warm for 8h. Cool the reactor to room temperature and filter. Wash the filter cake three times with purified water and dry it. Transfer the filter cake to a drying oven at 75°C and dry it to constant weight to obtain activated modified anti-aging particles.

[0058] Preparation Example 4

[0059] This preparation example provides a method for preparing benzophenone-modified polysiloxane, specifically as follows:

[0060] Weigh 9.7 g of 2-aminobenzophenone and 97 mL of tetrahydrofuran and add them to an argon-protected reaction flask. Stir the mixture and heat the flask to 50 °C. Add 21.7 g of 3-propyl isocyanate methyl diethoxysilane to the reaction flask and keep the mixture at this temperature for 60 min. Then, apply a negative pressure to the reaction flask to -0.075 MPa and remove low-boiling substances by vacuum distillation to obtain diethoxysilane-modified benzophenone.

[0061] In the reaction, the amino group in 2-aminobenzophenone undergoes an addition reaction with the isocyanate group in 3-propyl isocyanate-methyldiethoxysilane, generating a urea-linked structure. This links the benzophenone structure to the diethoxysilane structure, yielding diethoxysilane-modified benzophenone. This transforms the stable structure of benzophenone into a silane monomer capable of participating in siloxane system reactions. The benzophenone structure itself possesses an aromatic ring and a carbonyl conjugated structure, which, under the influence of an electric field, helps to disperse local energy, inhibit molecular chain damage, and reduce dielectric loss.

[0062] Weigh out 100g of octamethylcyclotetrasiloxane, 10g of tetramethyltetravinylcyclotetrasiloxane, 8g of dodecylmethyldiethoxysilane, 17g of diethoxysilane-modified benzophenone, and 5mL of 75wt% sulfuric acid and add them to a reaction flask. Stir the mixture and heat it to 85℃. Keep the mixture at this temperature for 2 hours. Add 5g of diallyltetramethyldisiloxane to the reaction flask and keep the mixture at this temperature for 4 hours. Cool the reaction flask to room temperature and add 3wt% sodium bicarbonate aqueous solution to adjust the pH of the system to 7. Allow the mixture to stand and separate the contents. Wash the oily substance three times with purified water and transfer it to a rotary evaporator with a water bath temperature of 85℃. Apply a negative pressure to -0.095MPa and remove low-boiling substances by vacuum evaporation to obtain benzophenone-modified polysiloxane.

[0063] In the reaction, octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane undergo ring-opening equilibrium polymerization and siloxane bond rearrangement under sulfuric acid catalysis to form a polysiloxane backbone. Dodecylmethyldiethoxysilane and diethoxysilane-modified benzophenone are incorporated into the polysiloxane system through hydrolysis condensation and siloxane bond exchange, resulting in a polysiloxane containing benzophenone groups, long-chain dodecyl and vinyl structures. The subsequent addition of diallyltetramethyldisiloxane primarily serves as a capping agent. Finally, neutralization with sodium bicarbonate, separation washing, and vacuum depressurization remove low-boiling substances, along with the removal of acidic catalyst, moisture, and unreacted small molecules, yields a structurally stable benzophenone-modified polysiloxane.

[0064] Preparation Example 5

[0065] This preparation example provides a method for preparing benzophenone-modified polysiloxane, specifically as follows:

[0066] Weigh 9.7 g of 2-aminobenzophenone and 97 mL of tetrahydrofuran and add them to an argon-protected reaction flask. Stir the mixture and heat the flask to 55 °C. Add 21.7 g of 3-propyl isocyanate methyl diethoxysilane to the reaction flask and keep the mixture at this temperature for 70 min. Then, apply a negative pressure to the reaction flask to -0.075 MPa and remove low-boiling substances by vacuum distillation to obtain diethoxysilane-modified benzophenone.

[0067] Weigh out 100g of octamethylcyclotetrasiloxane, 10-15g of tetramethyltetravinylcyclotetrasiloxane, 10g of dodecylmethyldiethoxysilane, 18.5g of diethoxysilane-modified benzophenone, and 6.5mL of 80wt% sulfuric acid. Add these to a reaction flask and stir. Heat the reaction flask to 90℃ and maintain the temperature for 2.5h. Add 6g of diallyltetramethyldisiloxane to the reaction flask and maintain the temperature for 4.5h. Cool the reaction flask to room temperature and add 4wt% sodium bicarbonate aqueous solution to adjust the pH of the system to 7.5. Allow the mixture to stand and separate the layers. Wash the oily substance three times with purified water and transfer it to a rotary evaporator with a water bath temperature of 90℃. Apply a negative pressure to -0.095MPa and remove low-boiling substances by vacuum evaporation to obtain benzophenone-modified polysiloxane.

[0068] Preparation Example 6

[0069] This preparation example provides a method for preparing benzophenone-modified polysiloxane, specifically as follows:

[0070] Weigh 9.7 g of 2-aminobenzophenone and 97 mL of tetrahydrofuran and add them to an argon-protected reaction flask. Stir the mixture and heat the flask to 60 °C. Add 21.7 g of 3-propyl isocyanate methyl diethoxysilane to the reaction flask and keep the mixture at this temperature for 80 min. Then, apply a negative pressure to the reaction flask to -0.075 MPa and remove low-boiling substances by vacuum distillation to obtain diethoxysilane-modified benzophenone.

[0071] Weigh out 100g of octamethylcyclotetrasiloxane, 15g of tetramethyltetravinylcyclotetrasiloxane, 12g of dodecylmethyldiethoxysilane, 20g of diethoxysilane-modified benzophenone, and 8mL of 85wt% sulfuric acid. Add these to a reaction flask and stir. Heat the reaction flask to 95℃ and maintain the temperature for 3h. Add 7g of diallyltetramethyldisiloxane to the reaction flask and maintain the temperature for 5h. Cool the reaction flask to room temperature and add 5wt% sodium bicarbonate aqueous solution to adjust the pH of the system to 8. Allow the mixture to stand and separate the layers. Wash the oily substance three times with purified water and transfer it to a rotary evaporator with a water bath temperature of 95℃. Apply a negative pressure to -0.095MPa and remove low-boiling substances by vacuum evaporation to obtain benzophenone-modified polysiloxane.

[0072] Example 1

[0073] This embodiment provides a low dielectric loss insulated cable based on cross-linked polyethylene, comprising several cable cores, a filler layer, a wrapping layer, an armor layer, and an outer sheath layer;

[0074] The filler layer fills the gaps between several cable cores to keep the cross-section of the cable core composed of several cable cores round and avoid structural eccentricity in the subsequent wrapping process; the filler layer is one or more of polypropylene filler rope, polyethylene filler strip, and low smoke halogen-free polyolefin filler rope.

[0075] The wrapping tape is wrapped around the outside of several cable cores filled by the filler layer. It is used to tighten and fix the stranded cable cores and the filler layer, so as to stabilize the overall structure of the cable core. The wrapping tape is made of polyester tape, and the thickness of a single layer of the wrapping tape is 0.05-0.20mm, with a wrapping overlap rate of 15-30%.

[0076] The armor layer is placed outside the wrapping layer to improve the cable's tensile, compressive, impact, and mechanical damage resistance. The thickness of the armor layer is 0.3-0.8 mm. The armor layer can be one of the following: galvanized steel tape armor layer, galvanized steel wire armor layer, aluminum alloy tape armor layer, or aluminum alloy wire armor layer.

[0077] The outer sheath is made of low-smoke halogen-free flame-retardant cable material extruded and wrapped around the outside of the armor layer. The thickness of the outer sheath is 2.8-3.2mm, and it is used to provide waterproof, moisture-proof, wear-resistant, corrosion-resistant and flame-retardant protection for the internal structure of the cable.

[0078] Example 2

[0079] This embodiment provides a manufacturing process for a low dielectric loss insulated cable core based on cross-linked polyethylene, specifically as follows:

[0080] Calcium stearate, ethylene bis-stearamide, dibutyl phthalate, antioxidant 1010, and antioxidant 168 are mixed evenly in a weight ratio of 5:3:4:2:1 to obtain the additives.

[0081] Weigh out the following by weight: 80 parts of low-density polyethylene, 15 parts of linear low-density polyethylene, 6 parts of activated modified anti-aging particles prepared in Preparation Example 1, 11 parts of benzophenone-modified polysiloxane prepared in Preparation Example 4, and 2 parts of additives. Add them to a mixer at 135°C, melt and mix for 10 minutes, cool to room temperature, pulverize, and pass through an 8-mesh sieve to obtain polyethylene premix.

[0082] The polyethylene premix was mixed evenly with 0.8 parts of di-tert-butyl peroxide isopropylbenzene and then added to a twin-screw extruder. The temperatures of the six temperature zones of the twin-screw extruder were set sequentially to 110℃, 115℃, 120℃, 125℃, 130℃, and 130℃. The mixture was melt-mixed for 40 seconds and then extruded to coat the outside of the conductor. After being thermally crosslinked at 175℃ for 6 minutes, the mixture was air-cooled and cured to form a crosslinked polyethylene insulation layer with a thickness of 3.0±0.1 mm on the outside of the conductor, thus obtaining the cable core.

[0083] In the cable core preparation process, low-density polyethylene and linear low-density polyethylene are first melt-mixed with activated modified anti-aging particles, benzophenone-modified polysiloxane, and additives to pre-disperse the functional components in the resin matrix. Subsequently, di-tert-butylperoxide is added. During extrusion coating and thermal crosslinking, the peroxide decomposes upon heating to generate free radicals. These free radicals further abstract hydrogen atoms from the polyethylene molecular chains, forming polyethylene macromolecular free radicals. These macromolecular free radicals undergo coupling reactions to form a carbon-carbon crosslinked structure, transforming the polyethylene from a linear or branched structure into a three-dimensional crosslinked network.

[0084] The alkenyl structure on the surface of the activated and modified anti-aging particles, as well as the vinyl and allyl structures in the benzophenone-modified polysiloxane, can also participate in free radical reactions, grafting or cross-linking with polyethylene segments to fix them. This embeds the functional particles and modified polysiloxane into the cross-linking network, making the functional components more stable in dispersion, the interface bonding stronger, reducing the migration and local enrichment of small molecules, and making the microstructure inside the insulation layer more uniform.

[0085] Example 3

[0086] This embodiment provides a manufacturing process for a low dielectric loss insulated cable core based on cross-linked polyethylene, specifically as follows:

[0087] Zinc stearate, ethylene bis-stearamide, dioctyl phthalate, antioxidant 1010, and antioxidant 168 are mixed evenly in a weight ratio of 5:3:4:2:1 to obtain the additives.

[0088] Weigh out the following by weight: 83 parts of low-density polyethylene, 17 parts of linear low-density polyethylene, 7 parts of activated modified anti-aging particles prepared in Preparation Example 2, 14 parts of benzophenone-modified polysiloxane prepared in Preparation Example 5, and 2.5 parts of additives. Add them to a mixer at 140°C, melt and mix for 13 minutes, cool to room temperature, pulverize, and pass through an 8-mesh sieve to obtain polyethylene premix.

[0089] The polyethylene premix was mixed evenly with 1.2 parts of di-tert-butylperoxyisopropylbenzene and then added to a twin-screw extruder. The temperatures of the six temperature zones of the twin-screw extruder were set sequentially to 113℃, 117℃, 123℃, 127℃, 133℃, and 133℃. The mixture was melt-mixed for 55 seconds and then extruded to coat the outside of the conductor. After being thermally crosslinked at 188℃ for 7 minutes, the mixture was air-cooled and cured to form a crosslinked polyethylene insulation layer with a thickness of 3.0±0.1 mm on the outside of the conductor, thus obtaining the cable core.

[0090] Example 4

[0091] This embodiment provides a manufacturing process for a low dielectric loss insulated cable core based on cross-linked polyethylene, specifically as follows:

[0092] Stearate, ethylene bis-stearamide, phthalate, antioxidant 1010, and antioxidant 168 are mixed evenly in a weight ratio of 5:3:4:2:1 to obtain the additives.

[0093] Weigh out the following by weight: 85 parts of low-density polyethylene, 18 parts of linear low-density polyethylene, 8 parts of activated modified anti-aging particles prepared in Preparation Example 3, 16 parts of benzophenone-modified polysiloxane prepared in Preparation Example 6, and 3 parts of additives. Add them to a mixer at 145°C, melt and mix for 15 minutes, cool to room temperature, pulverize, and pass through a 10-mesh sieve to obtain polyethylene premix.

[0094] The polyethylene premix was mixed evenly with 1.6 parts of di-tert-butylperoxyisopropylbenzene and then added to a twin-screw extruder. The temperatures of the six temperature zones of the twin-screw extruder were set sequentially to 115℃, 120℃, 125℃, 130℃, 135℃, and 135℃. The mixture was melt-mixed for 70 seconds and then extruded to coat the outside of the conductor. After being thermally crosslinked at 200℃ for 8 minutes, the mixture was air-cooled and cured to form a crosslinked polyethylene insulation layer with a thickness of 3.0±0.1 mm on the outside of the conductor, thus obtaining the cable core.

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 4 is that in Preparation Example 3, step 1 is omitted, and the magnesium-aluminum composite boron nitride in step 2 is replaced with boron nitride in step 1.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 4 is that in Preparation Example 3, step 3 is omitted, and the dopamine-modified particles prepared in step 2 are used instead of the activated modified anti-aging particles.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 4 is that in Preparation Example 6, diethoxysilane-modified benzophenone was not added.

[0101] Comparative Example 4

[0102] The difference between this comparative example and Example 4 is that in Preparation Example 6, dodecylmethyldiethoxysilane was not added.

[0103] Performance testing:

[0104] The cable cores prepared in Examples 2-4 and Comparative Examples 1-4 were used as test specimens for performance testing;

[0105] The dielectric loss tangent tanδ of the performance test sample's ethylene insulation layer was determined according to standard GB / T 3048.11-2025 "Test Methods for Electrical Performance of Wires and Cables - Part 11: Dielectric Loss Tangent Test" at 50Hz and 20℃.

[0106] The performance test sample was placed in an environment with a temperature of 105℃ and aged in hot air for 168h. The dielectric loss tangent tanδ of the olefin insulating layer of the performance test sample under the conditions of 50Hz and 105℃ was measured.

[0107] The volume resistivity of the olefin insulating layer of the performance test sample was determined in accordance with the standard GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistivity and volume resistivity".

[0108] The tensile strength and elongation at break of the test specimens were determined in accordance with the standard GB / T 2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 11: General Test Methods - Thickness and Dimensional Measurement - Mechanical Properties Test" before and after thermal aging at 105℃ for 168 hours. The specific test data are shown in Table 1 below.

[0109] Table 1 - Performance Test Data of Samples

[0110]

[0111] Data Analysis:

[0112] Comparative analysis of the data in Table 1 above shows that the volume resistivity of the cross-linked polyethylene insulation layer of the cable core prepared in Examples 2-4 of this invention reaches 6.2 × 10⁻⁶. 14 -7.1×1014 The dielectric loss tangent Tanδ is 1.5 × 10 Ω·m at 50 Hz and 20 °C. -4 -2.0×10 -4 After aging in hot air at 105℃ for 168 hours, its Tanδ still remained at 2.6×10. -4 -3.4×10 -4 The tensile strength retention rate reaches 90.1%-92.6%, and the elongation at break retention rate reaches 85.9%-90.5%. This indicates that the cable core prepared by this invention has low dielectric loss, high insulation resistivity, and good heat aging resistance.

[0113] Comparative Example 1 omitted the magnesium-aluminum composite boron nitride and used only boron nitride for subsequent reactions. Compared with Example 4, its volume resistivity decreased from 6.3 × 10⁻⁶. 14 Ω·m decreased to 5.1 × 10 14 Ω·m, initial Tanδ is 1.7×10 -4 Increased to 2.4 × 10 -4 After aging, Tanδ decreased from 2.9 × 10⁻⁶. -4 Increased to 4.5×10 -4 This indicates that the magnesium-aluminum composite layer has a significant effect on the surface activation and interfacial bonding of boron nitride. Without the magnesium-aluminum composite layer, the resistivity of the material decreases, the dielectric loss increases, and the mechanical retention rate after aging also declines.

[0114] Comparative Example 2 eliminated the activation modification step, replacing the activated anti-aging particles with dopamine-modified particles. The initial volume resistivity of this comparative example was 5.4 × 10⁻⁶. 14 Ω·m, initial Tanδ is 2.2×10 -4 The performance degradation was most significant after aging, with only 78.5% of the tensile strength and 69.5% of the elongation at break remaining after aging. The Tanδ increased to 5.2 × 10⁻⁶ after aging. -4 This indicates that hindered phenolic and alkenyl structures have a significant impact on the properties after thermal aging. Without hindered phenolic and alkenyl structures, the material is more prone to interfacial debonding and micro-defect propagation during aging, resulting in a significant decrease in both electrical and mechanical properties after aging.

[0115] Comparative Example 3 did not contain diethoxysilane-modified benzophenone. Compared to Example 4, its volume resistivity decreased from 6.3 × 10⁻⁶. 14 Ω·m decreased to 5.5 × 10 14 Ω·m, initial Tanδ is 1.7×10 -4 Increased to 2.5 × 10 -4 After aging, Tanδ decreased from 2.9 × 10⁻⁶. -4 Increased to 4.9 × 10 -4However, its mechanical properties change only slightly. This indicates that the main contribution of the benzophenone structure lies in electrical stability and low dielectric loss, rather than simply improving mechanical properties. Without the benzophenone structure, although polysiloxanes still possess flexibility and a certain degree of cross-linking ability, they are insufficient in suppressing molecular chain damage, local energy accumulation, and the increase in dielectric loss under the influence of an electric field.

[0116] Comparative Example 4, without the addition of dodecylmethyldiethoxysilane, has a volume resistivity of only 4.8 × 10⁻⁶. 14 Ω·m, the initial Tanδ reaches 2.8×10 -4 After aging, Tanδ reached 5.8 × 10⁻⁶. -4 Meanwhile, the tensile strength and elongation at break before and after aging are also relatively low. This indicates that the dodecyl segment is crucial for the compatibility and dispersion of benzophenone-modified polysiloxanes in polyethylene. Without long-chain alkyl groups, polysiloxanes are prone to phase separation or localized interfacial polarization regions in the polyethylene matrix, thus simultaneously affecting volume resistivity, dielectric loss, and mechanical continuity.

[0117] This study demonstrates that by synergistically modifying inorganic fillers and organosilicon functional components, activated modified anti-aging particles with insulating and thermally conductive properties, antioxidant protection, and the ability to participate in cross-linking fixation are obtained. Furthermore, benzophenone structures are incorporated into the polysiloxane system via silanization, forming benzophenone-modified polysiloxanes containing benzophenone electrically stabilizing groups, flexible siloxane segments, long-chain alkyl compatible segments, and unsaturated reactive groups. When these functional components are compounded with low-density polyethylene, linear low-density polyethylene, and peroxide cross-linking agents, they can be more stably dispersed and fixed within the polyethylene cross-linking network during thermal cross-linking. This reduces interfacial defects, polar oxidation products, and localized dielectric loss regions in the insulation layer, resulting in cable cores with higher volume resistivity, lower dielectric loss tangent, and better retention of mechanical properties after thermal aging.

[0118] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low dielectric loss insulated cable based on cross-linked polyethylene, comprising a plurality of cable cores, a filler layer, a wrapping layer, and an outer sheath layer, characterized in that, The cable core includes a conductor and a cross-linked polyethylene insulation layer covering the outside of the conductor; The cross-linked polyethylene insulation layer comprises the following components by weight: 80-85 parts of low-density polyethylene, 15-18 parts of linear low-density polyethylene, 6-8 parts of activated modified anti-aging particles, 11-16 parts of benzophenone-modified polysiloxane, 0.8-1.6 parts of initiator, and 2-3 parts of additives.

2. The low dielectric loss insulated cable based on cross-linked polyethylene according to claim 1, characterized in that, The preparation method of activated modified anti-aging particles is as follows: under the protection of an inert gas atmosphere, dopamine modified particles and anhydrous toluene are mixed and stirred. The reaction system is cooled to 0-5℃, and 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 4-chloropentenol and triethylamine are added to the reaction system. The mixture is kept warm and stirred for 90-120 min. The reaction system is then heated to 60-70℃ and kept warm for 6-8 h. After post-treatment, activated modified anti-aging particles are obtained.

3. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 2, characterized in that, The ratio of the dopamine-modified particles, anhydrous toluene, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride, 4-chloropentenol and triethylamine is 10g:500mL:1.0-1.2g:0.5-0.7g:1-1.6g.

4. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 2, characterized in that, The preparation method of dopamine-modified particles is as follows: magnesium-aluminum composite boron nitride and Tris buffer are mixed and ultrasonically dispersed for 30-50 min. Dopamine hydrochloride is added to the reaction system and stirred at room temperature for 6-8 h. After post-treatment, dopamine-modified particles are obtained.

5. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 4, characterized in that, The ratio of the magnesium-aluminum composite boron nitride, Tris buffer, and dopamine hydrochloride is 10g:800-1000mL:2-3g, and the concentration of the Tris buffer is 0.01mol / L with pH=8.

5.

6. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 4, characterized in that, The preparation method of magnesium-aluminum composite boron nitride is as follows: magnesium chloride, aluminum chloride and deionized water are mixed and stirred until the system is dissolved. Boron nitride is added to the reaction system and ultrasonically dispersed for 30-50 min. At room temperature, sodium hydroxide solution is added dropwise to the reaction system to adjust the pH of the system to 9-10. The reaction system is heated to 70-80℃ and allowed to stand for aging for 6-8 h. After post-treatment, magnesium-aluminum composite boron nitride is obtained.

7. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 6, characterized in that, The ratio of magnesium chloride, aluminum chloride, deionized water, and boron nitride used is 2-3g. 0.8-1.2g:100mL:15g, wherein the concentration of the sodium hydroxide solution is 0.3-0.5mol / L.

8. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 1, characterized in that, Benzophenone-modified polysiloxane is obtained by the following steps: A1. Under an inert gas atmosphere, 2-aminobenzophenone and tetrahydrofuran were mixed and stirred to dissolve. The reaction system was heated to 50-60℃, and 3-isocyanate methyl diethoxysilane was added to the reaction system. The reaction was kept at the temperature for 60-80 min. After post-treatment, diethoxysilane-modified benzophenone was obtained. A2. Mix and stir octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, dodecylmethyldiethoxysilane, diethoxysilane-modified benzophenone, and sulfuric acid. Heat the reaction system to 85-95℃ and keep it at that temperature for 2-3 hours. Add diallyltetramethyldisiloxane to the reaction system and keep it at that temperature for 4-5 hours. After post-treatment, benzophenone-modified polysiloxane is obtained.

9. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 8, characterized in that, In step A1, the ratio of 2-aminobenzophenone to tetrahydrofuran is 1g:10mL, and the molar ratio of 2-aminobenzophenone to 3-isocyanate methyldiethoxysilane is 1:1; in step A2, the ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, dodecylmethyldiethoxysilane, diethoxysilane-modified benzophenone, sulfuric acid, and diallyltetramethyldisiloxane is 100g:10-15g:8-12g:17-20g:5-8mL:5-7g, and the mass fraction of sulfuric acid is 75-85%.

10. A low dielectric loss insulated cable based on cross-linked polyethylene according to claim 1, characterized in that, The cable core is prepared as follows: low-density polyethylene, linear low-density polyethylene, activated modified anti-aging particles, benzophenone modified polysiloxane and additives are melt-mixed for 10-15 minutes, cooled to room temperature, and pulverized to obtain polyethylene premix; the polyethylene premix is ​​mixed evenly with an initiator and added to a twin-screw extruder, melt-mixed for 40-70 seconds, extruded and coated on the outside of the conductor, and then heat-crosslinked at 175-200℃ for 6-8 minutes and air-cooled to solidify, forming a crosslinked polyethylene insulation layer with a thickness of 3.0±0.1mm on the outside of the conductor.